Infection levels of Austrodiplostomum compactum (Digenea, Diplostomidae) metacercariae in Plagioscion squamosissimus (Teleostei, Sciaenidae) from the Nova Avanhandava reservoir, São Paulo State, Brazil - Paes, J. V. K. [UNESP]; Carvalho, Edmir Daniel [UNESP]; da Silva, R. J. [UNESP] (Cambridge University Press, 2010)
This study was aimed at evaluating the infection levels of Austrodiplostomum compactum metacercariae in 378 specimens of Plagioscion squamosissimus ('corvina' or 'pescada branca') from the Nova Avanhandava reservoir, low Tiete River, São Paulo State, Brazil. High prevalence, mean intensity of infection and abundance were observed in P. squamosissimus during most of the study, with the exception of March 2004. The relative condition factor (Kn) did not differ between parasitized and non-parasitized fish. A statistically significant positive correlation was observed between host standard length and intensity of infection. The analysis of biotic and abiotic variables showed that no abiotic variable correlated with parasitic infection levels. Moreover, P. squamosissimus status was demonstrated to be unaffected by A. compactum metacercariae infection.